Exploring the Role of Action Consequences in the Handle-Response Compatibility Effect - Scerrati, Elisa; D’Ascenzo, Stefania; Lugli, Luisa; Iani, Cristina; Rubichi, Sandro; Nicoletti, Roberto (Frontiers in Human Neuroscience, 2020)
Previous research investigating handle-response compatibility effects with graspable objects used different categories of objects as stimuli, regardless of their specific, intrinsic characteristics. The current study explores whether different types of objects’ characteristics may elicit different types of spatial compatibility, that is, handle-response and response-effect compatibility as well as their potential interaction. In Experiment 1, objects having a graspable handle opposite to either a visible functional component (i.e., handle-function objects: a teapot) or a latent functional component (handle-only objects: a pitcher lacking the spout) were presented separately in different blocks. Both the handle and the goal-directed functional components of these objects were located on the horizontal axis. In Experiment 2, handle-only objects had a handle located on the horizontal axis and a latent functional component located on the vertical axis (e.g., a cup). In both experiments, participants were required to judge the material (plastic, metal) the object was made of. Results showed that the handle-response compatibility effect was sensitive to whether the actions consequences of object manipulation took place on the horizontal rather than on the vertical axis.